Suboptimal guideline-directed medical therapy and prognosis in patients with heart failure and reduced ejection fraction: The SMYRNA Study - Kocabas, U.; Ergin, I.; Kivrak, T.; Oztekin, G. M. Yilmaz; Tanik, V. O.; Ozdemir, I. H.; Yeni, M. (Oxford Univ Press, 2023)
[Abstract Not Available]
Annual Meeting of the European-Society-of-Cardiology (ESC) -- AUG 25-28, 2023 -- Amsterdam, NETHERLANDS